Оригінальні зображення та реконструкції княжого герба І. Мазепи - Мезенцев, В.І. (Сіверщина в історії України, 2022)
Стаття вперше узагальнює усі відомі натепер графічні та рельєфні зображення князівського герба гетьмана Івана Мазепи XVIII–XXI ст. Ілюструються, описуються, аналізуються і порівнюються оригінальні опубліковані версії його геральдичної емблеми на гравюрі «Великого всезагального гербовника» (Нюрнберг, 1887), на кахлях з опорядження печей розкопаної резиденції генерального писаря Пилипа Орлика в м. Батурині Чернігівської обл. та на срібній печатці 1707–1708 рр. із зібрання Музею Шереметьєвих у Києві. Їх визнано достовірними й незаперечними візуальними свідченнями, які доповнюють обмежені австрійські та німецькі писемні повідомлення про князівське достоїнство І. Мазепи, пожалуване йому 1707 р. Особлива увага приділена дослідженню ще малознаних ранньомодерних геральдичних символів княжої влади української та європейської традицій. Розглядаються також спроби істориків і митців XIX–XX ст. графічно відтворити поліхромний герб того гетьмана як князя Священної Римської імперії та найбільш обґрунтовані й детальні його кольорові реконструкції, виготовлені технікою комп’ютерної графіки і опубліковані у 2019–2022 рр. Реконструйовані пічні кахлі з розкопок Батурина та одночасна печатка, введена до наукового обігу 2021 р., з унікальними бароковими композиціями і оформленням князівської емблеми І. Мазепи віднесено до цінних творів геральдичного мистецтва Гетьманщини його доби. Виявляються їхні українські та запозичені західні владні інсигнії й декоративні прийоми, виконані місцевими майстрами на замовлення гетьмана і П. Орлика. This article for the first time examines all of the graphic and relief representations of the princely armorial bearings (“herb”) of the Ukrainian Cossack ruler, Hetman Ivan Mazepa (1687–1709), which were prepared between the eighteenth and twenty first centuries and are known by the present. It demonstrates with figures, describes, analyses, and compares the original published designs of his heraldic emblem on the engraving at Johann Siebmacher’s, Grosses und allgemeines Wappenbuch: Fürsten des Heiligen Römischen Reiches: M–Z. Band I. 3. III. Nürnberg, 1887 (Great and Universal Collection of Coat of Arms), on the glazed ceramic tiles (“kakhli”) facing stoves at the residence of Chancellor General Pylyp Orlyk in the town of Baturyn, and on the silver seal of 1707–1708 from the collection of the Sheremet’iev Museum in Kyiv. Special attention is devoted to exploring the hitherto little known early modern heraldic symbols of a princely power (“korony, mantii”) of the Ukrainian and Western traditions. The fragments of these stove tiles were discovered during the 2017– 2020 excavations of the remnants of P. Orlyk’s home in Baturyn, Chernihiv province, Ukraine, which was the capital city of the seventeenth-and eighteenth-century Cossack state or Hetmanate. This Canada-Ukraine archaeological project is sponsored by the Canadian Institute of Ukrainian Studies (CIUS) at the University of Alberta and the Ucrainica Research Institute in Toronto, Canada. The Baturyn project is administered by The Peter Jacyk Centre for Ukrainian Historical Research at CIUS Toronto Office (https://www.ualberta.ca/canadian-institute-of-ukrainian-studies/ centres-and-programs/jacyk-centre/baturyn-project.html). The Ukrainian Studies Fund in New York, the Chernihiv Oblast State Administration, and the Vasyl Tarnovsky Chernihiv Regional Historical Museum support the archaeological and historical investigations of early modern Baturyn with annual grants. The most generous private benefactors of this project are the late artist Roman J. Wasylyszyn (Philadelphia, PA, USA), artist Ralph C. Roe II (Greenwich, CT, USA), Dr. George J. Iwanchyshyn, and Ms. Love Helen Negrych (Toronto). The author has shown that these original heraldic graphical, archaeological, and sphragistic sources represent the veracious indisputable visual evidence of the legitimate princely status of I. Mazepa. They corroborate and substantially supplement the limited and divergently interpreted by some historians the eighteenth- and nineteenth-century Austrian and German written archival and published information that in 1707 Kaiser Joseph I of the Holy Roman Empire of the German Nation honoured this Ukrainian hetman with the prestigious title of prince of this empire (“Sacri Romani Imperii Princeps” in Latin or “Reichsfürst” in German) for his vigorous defence of Christendom against Ottoman expansion. This article also reviews the obsolete hand-drawn versions by the nineteenth- and twentieth-century historians and artists attempting to recreate the polychrome coat of arms of I. Mazepa as imperial prince. It focuses on the more advanced, detailed, and grounded in sources recent reconstructions of his multicoloured armorial bearings prepared with the computer graphic technique. They are based on the close research of authentic relief depictions preserved on the 1707–1708 stove tiles excavated in Baturyn and on the synchronous silver seal from the Sheremet’iev Museum in Kyiv. These locally manufactured artefacts featuring unique compositions and decorations of I. Mazepa’s princely arms are valuable and informative examples of the Ukrainian baroque heraldic art. Their study and reconstructions provide an important new insight into the heraldry and representative culture of the Cossack elite and its European connections, which are the popular topics of current Ukrainian historical scholarship.